Structured systems analysis : tools and techniques - Gane, Chris (Prentice Hall Englewood CliffsUS, 1979)
Discusses problems faced in systems analysis and stresses need for new tools. Examines graphical tools showing how they fit together to make a logical model. Identifies tools needed to make a logical model. These include the data flow diagram, data dictionary, the logic of processes and data stores. Presents a structured systems development methodology which takes advantage of the new tools. Shows how to derive a structured design from the logical model and examines issues that arise in changing over to these new techniques from the traditional approaches. Contains exercises and discussion points after each chapter and glossary of terms at end of text.